MRI tagging of colonic chyme mixing in healthy subjects: Inter‐observer variability and reliability of the measurement with time - Alshammari, Meshari T.; Alyami, Ali S.; Wilkinson‐Smith, Victoria; Spiller, Robin C.; Gowland, Penny; Marciani, Luca; Moran, Gordon W.; Hoad, Caroline L. (Neurogastroenterology and motility, 2023)
Background Magnetic resonance imaging (MRI) tagging techniques have been applied to the GI tract to assess bowel contractions and content mixing. We aimed to evaluate the dependence of a tagging measurement (for assessing chyme mixing) on inter‐observer variability in both the ascending colon (AC) and descending colon (DC) and to investigate the temporal variation and hence reliability of the colonic tagging technique by acquiring multiple measurements over time on healthy participants. Methods Two independent datasets of healthy adults were used for the retrospective inter‐observer variability (Study 1: 13 datasets and Study 2: 31 datasets), and ten participants were scanned for the prospective temporal variation study following a 1 L mannitol oral preparation. All colonic tagging data were acquired on 3 T MRI scanners. The mean and the standard deviation (SD) maps were generated pixel‐by‐pixel using custom‐written software in MATLAB. The colonic regions of interest were defined using MIPAV software. Bland–Altman plots and scatter plots were used for the inter‐observer variability. The mean and SD of all repeated measures for each subject were calculated along with a one‐way ANOVA to test for variations with time. Results Scatter plots and Bland–Altman plots showed a large range of data with low variation and small limits of agreements (<5% CoV). The intraclass correlation coefficient of inter‐rater reliability was excellent and 0.97 or above for the AC and DC measurements for both datasets. The temporal variation study shows that there was no significant difference found between the multiple measures with time (p = 0.53, one‐way repeated measures ANOVA test). Conclusions MRI tagging technique can provide an assessment of colonic chyme mixing. The inter‐observer study data showed high inter‐rater agreement. The temporal variation study showed some individual variations with time suggesting multiple measurements may be needed to increase accuracy. We aimed in this study to evaluate the dependence of a tagging measurement (for assessing chyme mixing) on inter‐observer variability in both the ascending colon and descending colon and to investigate the temporal variation and hence reliability of the colonic tagging technique by acquiring multiple measurements over time on healthy participants.